The contingency of unequal power relations in marriage - Dowling, Dolina (Acta Academica: Critical views on society, culture and politics, 2024)
In the traditional marriage there is an unequal power relationship between the spouses. The husband is in the dominant role and his wife is subordinate to him. Presumably this state of affairs would be justified if a relevant universal difference could be found between men and women such as would entail male domination. Can such a difference be found? This paper considers some of the affirmative claims from che Christian tradition, from Aristotle, from Rousseau, and (more particularly) in recent years from sociobiologists concerning the natural tendencies of the respective .genders - claims which aim to justify male domination. le then briefly considers and rejects the claim that even if there are no relevanc natural differences that justify the unequal power relationship in marriage, someone has to have the power in the relationship. Lastly, I suggest that an equitable marriage where husband and wife have equal power is to be preferred.